Painting by numbers : data-driven histories of nineteenth-century art - Greenwald, Diana, 1989- (Princeton University Press, 2021)
"An innovative application of economic methods to the study of art history, demonstrating that new insights can be uncovered by using quantitative and qualitative methods together, which sheds light on longstanding disciplinary inequities"--